Effect of Organic Acid Blends in Drinking Water on Growth Performance, Blood Constituents and Immune Response of Broiler Chickens - Marín Flamand, Ernesto; Vásquez Durán, Alma; Méndez Albores, Abraham (2014)
This research was conducted to evaluate the effect of organic acid blends (OAB) of ascorbic (A), citric (C), malic (M), sorbic (S), and tartaric (T) acids provided through the drinking water on growth performance, blood constituents, and immune response of broiler chickens from hatch to 42 d of growth. Three-hundred 1-d-old Ross broiler chickens were randomly divided into 4 treatment groups (1 control and 3 experimental) of 5 replicates (15 birds per replicate). Control group was given ordinary water and treatments were given continuously the acidified water using three different blends consisting of: OAB1＝A:C:M, OAB2＝A:S:M, and OAB3＝A:T:M. Blends were prepared with ratio 35:60:5 and were used at a concentration of 0.5% (wt/vol). The results showed that all OAB had no significant effect on live body weight (LBW); however, an improvement on feed consumption (FC), feed conversion ratio (FCR), and survival rate (SR) were observed as compared to the control. Birds supplied with OAB1 presented the lowest FCR (1.803), FC (96.19 g/bird/day), and the highest SR (95.63%). Blood constituents (hematocrite, total protein, and albumin), enzymatic activity (gamma glutamyl transpeptidase and aspartate aminotransferase), immune response, organs weight, and pH values of different gastrointestinal tract segments were not affected by administering the OAB. However, reductions in the alanine aminotrasferase activity and an increment in the aspartate aminotransferase:alanine aminotrasferase ratio were observed in groups provided with the OAB1 and OAB3, respectively. From these results, it is concluded that OAB1 could be used as an alternative for improving FC, FCR, and SR in broiler chickens